(untitled) (Contemporary Education and Teaching Research, 2023)
Educational institutions and schools play key roles and responsibilities in the context of integrating career planning and innovation and entrepreneurship education. The development of innovation and entrepreneurship education promotes career planning and provides broad career development opportunities, practice opportunities, and the development of autonomous thinking. Educational institutions and schools should design curricula that integrate with innovation and entrepreneurship education, provide career counseling and guidance services, and encourage students to participate in hands-on and practical projects to develop innovation and entrepreneurial spirit and skills. Through students’ participation and practice, they can develop practical work competencies, master key skills, and achieve self-development and growth. The efforts of educational institutions and schools will provide a solid foundation for students’ career development and innovative and entrepreneurial paths.